2022
DOI: 10.1136/bmjopen-2021-060077
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising paediatric advance care planning: a qualitative phenomenological study of paediatricians caring for children with life-limiting conditions in Australia

Abstract: ObjectivesAdvance care planning (ACP) helps families and paediatricians prepare and plan for end-of-life decision-making. However, there remains inconsistency in its practice with the limited literature describing what this preparation involves, and whether paediatricians recognise a difference between the process of ACP and its outcomes, such as resuscitation plans. This study aims to understand how paediatricians conceptualise ACP when caring for children with life-limiting conditions (LLC) who are unable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Community nurses in this review were reported to avoid initiating ACP conversations in situations of family conflict (i.e., denial) [ 52 , 60 ] or where family dynamics (i.e., differing priorities) complicated the process [ 52 , 54 , 64 ]. Similarly, in paediatrics, parents and/or carers in denial of a child’s palliative condition presented challenges initiating ACP [ 77 ], despite the benefit of ACP preparing families for end-of-life care [ 78 ]. However, from this review, Glaudemans et al [ 53 ] mentioned educating families about ACP benefits and building decision-making confidence (e.g., explaining an Advance Care Plan can be amended to reflect changes in care), as well as the confidence of community nurses can help to ameliorate these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Community nurses in this review were reported to avoid initiating ACP conversations in situations of family conflict (i.e., denial) [ 52 , 60 ] or where family dynamics (i.e., differing priorities) complicated the process [ 52 , 54 , 64 ]. Similarly, in paediatrics, parents and/or carers in denial of a child’s palliative condition presented challenges initiating ACP [ 77 ], despite the benefit of ACP preparing families for end-of-life care [ 78 ]. However, from this review, Glaudemans et al [ 53 ] mentioned educating families about ACP benefits and building decision-making confidence (e.g., explaining an Advance Care Plan can be amended to reflect changes in care), as well as the confidence of community nurses can help to ameliorate these issues.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the same in paediatric ACP since the parents as the decision-makers are not ill and are not going to lose their decision-making capacity. The motivation of paediatric ACP is to prepare parents (Vemuri et al, 2022). However, not all parents find this preparation acceptable (Liberman et al, 2014; Mitchell et al, 2019), and the challenge for paediatricians is to identify how much to engage parents in these discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced care planning is a process which aims to improve the quality of patients’ end-of-life period by supporting them to make choices consistent with their values and goals of care [ 11 , 12 ]. It empowers families to better understand and honour the individual’s preferences [ 13 ].…”
Section: Introductionmentioning
confidence: 99%